Anti-Inflammatory Effects of Nephelium lappaceum Peel Extract and Geraniin on External Skin Stimulation - Eun-Jeong Lee; Soo-Mi Ahn; Youn-Hee Nam; Myo-Deok Kim; Chan-Song Jo; Bin-Na Hong; Youn-Ki Cho; Jae-Sung Hwang (Cosmetics)
Geraniin is the major compound in Nephelium lappaceum peel and exhibits significant immunomodulatory effects. So, this study aimed to evaluate the anti-inflammatory effects of Nephelium lappaceum peel extract and geraniin through in vitro experiments and clinical trials. In vitro, inflammatory responses were induced using UV, IR, SDS, LPS, and RA, followed by treatment with the Nephelium lappaceum peel extract and geraniin. The results demonstrated significant reductions in inflammatory cytokines, indicating potent anti-inflammatory properties. Based on these promising results, clinical trials were conducted to assess the effects of the Nephelium lappaceum peel extract on skin barrier function using various irritants, including IR, UV, SDS, Retinol, and tape stripping. Measurements of transepidermal water loss and erythema were performed to evaluate the extract’s protective effects. The results indicated that Nephelium lappaceum peel extract effectively mitigated skin barrier damage and reduced erythema, confirming its potential as a skin-soothing and anti-inflammatory agent. This study suggests that Nephelium lappaceum peel extract, rich in bioactive compounds such as geraniin, can be utilized in the development of cosmetic products aimed at reducing skin inflammation and protecting against environmental irritants.